Reliability measure of the rib cage deformity by a postural assessment software in patients with adolescent idiopathic scoliosis - Bruna Marques de Almeida Saraiva; Thais Moraes de Vieira; Anderson Sales Alexandre; Geferson da Silva Araújo; Evandro Fornias Sperandio; Victor Zuniga Dourado; Liu Chiao Yi; Milena Carlos Vidotto (Universidade Federal de Santa Catarina, 2020)
Adolescent idiopathic scoliosis (AIS) is a three-dimensional deformity of the spine that generates changes in the biomechanics of the rib cage. Digital photogrammetry enables the recording of subtle changes and the interrelationship between parts of the human body that are difficult to measure by other means. The aim of this study was to create angles and thoracic distances and to evaluate the interobserver and intraobserver reliability of these measurements using the Software de Avaliação Postural (SAPO) in patients with AIS. This cross-sectional study evaluated 30 individuals aged between 11 and 18 years with AIS. We used SAPO with the thoracic markers in the form of angles (A) and distances (D) with involves structures like acromion, manubrium, xiphoid process, lower angle of the scapula, last false rib, anterior iliac spine process. Two experienced observers (A and B) analyzed the photos and all followed the same routine of analysis. Intraobserver and interobserver reproducibility was assessed by the Bland-Altman plot and intraclass correlation coefficient (ICC), while intraobserver and interobserver reliability was assessed by the T-Test and Wilcoxon's Test. A high repeatability index was obtained among the evaluations, with twelve of the sixteen variables considered as reliable in all statistical tests. The interobserver analyzes presented excellent correlation coefficients (ICC), showing good reliability for six of the sixteen variables proposed. The SAPO method presented good reproducibility and reliability for most of the thoracic markers created, showing that photogrammetry may be a complementary tool in the evaluation of thoracic alterations in patients with AIS.